Minimizing carry-over PCR contamination in expanded CAG/CTG repeat instability applications. Issue 1 (December 2017) - Aeschbach, Lorène; Dion, Vincent
Abstract Expanded CAG/CTG repeats underlie the aetiology of 14 neurological and neuromuscular disorders. The size of the repeat tract determines in large part the severity of these disorders with longer tracts causing more severe phenotypes. Expanded CAG/CTG repeats are also unstable in somatic tissues, which is thought to modify disease progression. Routine molecular biology applications involving these repeats, including quantifying their instability, are plagued by low PCR yields. This leads to the need for setting up more PCRs of the same locus, thereby increasing the risk of carry-over contamination. Here we aimed to reduce this risk by pre-treating the samples with a UracilN -Glycosylase (Ung) and using dUTP instead of dTTP in PCRs. We successfully applied this method to the PCR amplification of expanded CAG/CTG repeats, their sequencing, and their molecular cloning. In addition, we optimized the gold-standard method for measuring repeat instability, small-pool PCR (SP-PCR), such that it can be used together with Ung and dUTP-containing PCRs, without compromising data quality. We performed SP-PCR on myotonic-dystrophy-derived samples containing an expansion as large as 1000 repeats, demonstrating the applicability to clinically-relevant material. Thus, we expect the protocols herein to be applicable for molecular diagnostics of expanded repeat disorders.